Bentuk Gerak Pajaga Bone Balla Anaddara Sulessana di Kedatuan Luwu - Nurwahidah Nurwahidah; Muhammad Suyudi (Seminar Nasional LP2M UNM, 2022)
Abstract. Pajaga Bone Balla Anaddara (PBBA) research is a tracking to uncover the concept of Pajaga Bone Balla Anaddara as an art form (art of movement/dance), using an ethnochoreological approach in dissecting PBBA textually and contextually, which is supported by several theories and written descriptively qualitatively Form theory is used to reveal integrated elements into a unified whole as a form of PBBA dance performance. The results of the study show that PBBAS has a form of movement that is inseparable from the rules in the Kedatuan Luwu palace which are summarized in the variety of movements, descriptions of movements and floor patterns of PPBA Sulessana Keywords: Art, Dance, Shape, Movement, Pajaga